2019
DOI: 10.26858/ijfs.v5i2.11108
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Parameter Biofisik Perairan dengan Hasil Tangkapan Ikan Pelagis Kecil di Perairan Pulau Ternate

Abstract: This research was experimental fishing methods and regression analysis to examine the effect and relationship between biophysical parameters namely sea surface temperature and chlorophyll-a and the results of small pelagic fish conversations in Ternate Island, the results of the study showed that the biosphysical parameters including sea surface temperature (SPL) and chlorophyll-a have a significant influence on the distribution of small pelagic fish, with the correlation coefficient values of each sea surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The optimal sea surface temperature for the capture of small pelagic fish, based on research by Safruddin et al (2018) in the Bone Bay Waters, is in the range of 29-33°C. Another study conducted in the waters around Ternate Island reported that the sea surface temperature in the small pelagic fish capture area ranged from 25 to 33°C (Naim et al, 2019).…”
Section: Oceanographic Parameters Of Sodo' Fishing Groundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal sea surface temperature for the capture of small pelagic fish, based on research by Safruddin et al (2018) in the Bone Bay Waters, is in the range of 29-33°C. Another study conducted in the waters around Ternate Island reported that the sea surface temperature in the small pelagic fish capture area ranged from 25 to 33°C (Naim et al, 2019).…”
Section: Oceanographic Parameters Of Sodo' Fishing Groundsmentioning
confidence: 99%
“…Karuwal (2020) in Imran Abu Ziyad, et al ( 2022) stated that salinity affects the metabolic system of fish, playing a role in gas and fluid exchange within the fish's body. According to Naim et al (2019), small pelagic fish are often caught at salinity levels of 32.7 to 33.7 ppt. Similarly, a study by Kusuma Pradika Candra M, et al ( 2014) conducted in Morodemak waters found that catches of Stolephorus spp.…”
Section: Oceanographic Parameters Of Sodo' Fishing Groundsmentioning
confidence: 99%